Shear Bond Strength of Simulated Single-Retainer Resin-Bonded Bridges Made of Four CAD/CAM Materials for Maxillary Lateral Incisor Agenesis Rehabilitation - Calheiros-Lobo, Maria João; Calheiros-Lobo, João Mário; Carbas, Ricardo; da Silva, Lucas F. M.; Pinho, Teresa (European Journal of Dentistry, 2023)
Objectives Maxillary lateral incisor agenesis (MLIA), treated orthodontically by space opening, requires complimentary aesthetic rehabilitation. Resin-bonded bridges (RBBs) can be equated as interim rehabilitation until skeletal maturity is achieved to place an implant-supported crown or as definitive rehabilitation in case of financial restrictions or implant contraindications. Scientific evidence of the best material must be confirmed in specific clinical situations. Computer-aided design and computer-aided manufacturing (CAD/CAM) materials are promising versatile restorative options. This study aimed to identify a straightforward material to deliver interim or definitive RBBs for nonprepared tooth replacement in MLIA.Materials and Methods Single-retainer RBB made from CAD/CAM ceramic blocks (Vita Enamic [ENA], Suprinity [SUP], and zirconia [Y-ZPT]) and a three-dimensional (3D) printed material (acrylonitrile butadiene styrene [ABS]) were evaluated by shear bond strength (SBS) and mode of failure, after adherence to an artificial tooth with RelyX Ultimate used in a three-step adhesive strategy.Statistical Analysis The load to fracture (N) was recorded, and the mean shear stress (MPa) was calculated with standard deviations (SD) for each group and compared between materials using boxplot graphics. One-way analysis of variance (ANOVA) followed by the Tukey–Kramer post hoc test was used to compare the differences (α = 0.05). A meta-analysis focusing on CAD/CAM materials evaluated the magnitude of the difference between groups based on differences in means and effect sizes (α = 0.05; 95% confidence interval [CI]; Z-value = 1.96). Failure mode was determined by microscopic observation and correlated with the maximum load to fracture of the specimen.Results The mean ± SD SBS values were ENA (24.24 ± 9.05 MPa) < ABS (24.01 ± 1.94 MPa) < SUP (29.17 ± 4.78 MPa) < Y-ZPT (37.43 ± 12.20 MPa). The failure modes were mainly adhesive for Y-ZPT, cohesive for SUP and ENA, and cohesive with plastic deformation for ABS.Conclusion Vita Enamic, Suprinity, Y-ZPT zirconia, and 3D-printed ABS RBBs are optional materials for rehabilitating MLIA. The option for each material is conditioned to estimate the time of use and necessity of removal for orthodontic or surgical techniques.
Keywords: 3D additive manufacturing; adhesion; CAD/CAM; maxillary lateral incisor agenesis; monolithic ceramics; shear bond strength; surface energy